USE OF INFORMATION TECHNOLOGY IN THE PANDEMIC TIME OF COVID-19 (CASE STUDY AT TPI DENPASAR CLASS I IMMIGRATION OFFICE) - I Komang Adika Pranata (Polteknik Imigrasi, 2020)
The Covid-19 pandemic has made a transform in work culture that is done directly now to switch to providing services through an online-based system. Work system policies during the pandemic period are always changing and developing. The use of information technology is an option during the Covid-19 pandemic to minimize interactions with fellow humans and disentangle the crowd. This study aims to explain how the application of information technology during the Covid-19 pandemic, especially at the Denpasar Immigration Office of Border Control. The research method used in this research is descriptive qualitative method. The focus of this research is on the Denpasar Immigration Office of Border Control and Immigration Checkpoint in the seaport of Benoa. The results of this study can be seen that in general the use of information technology during the Covid-19 pandemic at the Denpasar Immigration Office of Border Control is a zoom meeting, simpeg kumham, sisumaker, applications and information systems on immigration techniques and the use of social media as a medium for disseminating immigration information. Researchers hope that they always carry out maintenance of hardware and software so that they can run optimally during the Covid-19 pandemic and always evaluate the use of information technology.